O-51 Occupational exposure to triazole fungicides and risk of prostate cancer in the AGRIculture and CANcer (AGRICAN) cohort. (14th March 2023) - Juliette, Hippert; Marine, Renier; Séverine, Tual; Mathilde, Bureau; Anne-Valérie, Guizard; Elisabeth, Marcotullio; Mathilde, Boulanger; Isabelle, Baldi; Pierre, Lebailly
Abstract : Introduction: Prostate cancer incidence ranks 2nd among men worldwide. Farming and pesticide use are associated with prostate cancer risk. Triazole fungicides are widely used in agriculture to fight against several crop diseases such as odiumn scab, rot… Some are carcinogenic on animals, many are endocrine disruptors and most of them were never studied in epidemiology. Material and Methods: Data on pesticide use on 10 crops, including years of beginning and ending, were collected in 2005–2007 for 81, 960 men from the enrolment questionnaire of AGRICAN. Incident prostate cancer cases were identified through linkage with cancer registries. Exposure to 26 triazole fungicides was assessed using the crop-exposure matrix PESTIMAT (Baldi, 2017). Hazard Ratios (HR and 95%CI) were estimated using Cox models with attained age as time scale. Results: Until 2017, we identified 4, 654 incident prostate cancer cases among AGRICAN men. 42, 316 men were exposed to pesticides and 21, 645 to at least one of the 26 triazole fungicides. An elevated prostate cancer risk was found with azaconazole -used on fruit growing beteween 1995 and 2003 (HR=1.21, p=0.12), with no duration effect. We also found a tendency of excess risk with exposure to myclobutanil (used on vineyard and fruit growing) for use exceeding 30 years (HR=1.43, p=0.20), and to penconazole (used on vineyard, fruit growing and tobacco) for a duration of use between 30 and 40 years (HR=1.65, p=0.16). In contrast, we found a tendency of decreased risk for exposure to tebuconazole during more than 40 years (HR=0.70, p=0.19), and for short exposure duration to triadimenol (HR<10 years=0.88, p=0.18). Conclusions: Considering ever/never exposure, we found few associations between prostate cancer and triazoles. We will assess exposure more in depth with the calculation of life-long cumulated scores score exposure (probability x frequency x intensity), especially for triazoles associated with prostate cancer in the present analysis.